Genome-wide characterization of BPC transcription factors in pear and functional validation of PbBPC5 in drought tolerance regulation - Jia, Xin; Han, Xing; Cheng, Yuan; Ren, Xiaoli; Fan, Guiyan; Jiao, Xiaocong; Cai, Yueyue; Li, Lu; Zhang, Chenwei; Pang, Hongguang (Frontiers in Plant Science, 2026)
IntroductionThe BASIC PENTACYSTEINE (BPC) family comprises plant-specific transcription factors that regulate diverse developmental programs and stress responses. Pear (Pyrus bretschneideri), an economically significant fruit crop, often experiences marked declines in fruit yield and quality under drought stress. Although BPC genes have been identified in several plant species, a comprehensive characterization of this family in pear is lacking.MethodsIn this study, we systematically characterized PbBPC genes in the pear genome using various bioinformatic approaches. We examined their expression profiles across diverse tissues and under dehydration conditions and further validated the role of PbBPC5 in drought tolerance using virus-induced gene silencing (VIGS).ResultsThis study identified seven PbBPC genes in the pear genome, which were subsequently classified into three distinct groups through phylogenetic analysis. Comprehensive bioinformatics analyses were performed, examining their phylogenetic relationships, gene structures, conserved motifs, protein domains, chromosomal locations, and gene duplication events. Promoter analyses showed that all PbBPC genes contained various cis-acting elements associated with growth and development, stress response, and phytohormone signaling. Quantitative real-time PCR (qRT-PCR) showed that most PbBPC transcripts were upregulated by dehydration, with PbBPC5 exhibiting the strongest upregulation. Furthermore, subcellular localization experiments indicated that PbBPC5 was localized to the nucleus. Silencing PbBPC5 reduced drought tolerance, as indicated by more severe wilting under water deficit, lower relative water content, higher electrolyte leakage, and elevated malondialdehyde levels. PbBPC5 silencing also weakened antioxidant defenses during drought by reducing antioxidant enzyme activities. These results suggest that PbBPC5 functions on drought tolerance regulation in pear mainly by influencing reactive oxygen species scavenging.DiscussionThis study provides a genome-wide characterization of the PbBPC family and reveals PbBPC5 as a key regulator of the drought response, offering a foundation for improving pear drought tolerance through genetic approaches.